Observations on the morphology of the ovaries of the porcupine (Hystrix cristata) - Ozdemir, Dervis; Aydin, Ali; Yilmaz, Sadik; Dinc, Gursel; Atalar, Omer (My University, 2005)
This study was carried out in order to investigate the structure of ovaries of the porcupine (Hystrix cristata). Ovaries were obtained by laparoscopic surgery and were then divided into two sections and fixed in buffered formalin. The sections (5-7 ?m) were cut in paraffin blocks, stained with Mayer's haematoxylin stain, Crossmonn's triple stain and McManus's periodic acid Schiff (PAS) technique. In histological examinations it was composed of two main zones, cortex and medulla. The surfaces of the ovaries were wavy and lined by simple cuboidal or columnar epithelium. The tunica albuginea consisted of connective tissue fibres. There were connective tissue cells in the cortex, as well as interstitial cells containing lipid. Primordial, primary, secondary, tertiary follicles, corpus luteum and atretic follicles were seen in the cortex of ovaries. Mean diameters of these follicles varied between 80 and 1600 ?m. Medulla consisted of loose connective tissue which contained blood and lymph vessels of varying sizes. The masses and sizes - length, width and thickness - of the right and left ovaries were almost the same.
Keywords: Hystrix cristata; Ovary; Porcupine; Structure